Enhanced stability and thermoelectric figure-of-merit in copper selenide by lithium doping. (June 2017) - Kang, Stephen Dongmin; Pöhls, Jan-Hendrik; Aydemir, Umut; Qiu, Pengfei; Stoumpos, Constantinos C.; Hanus, Riley; White, Mary Anne; Shi, Xun; Chen, Lidong; Kanatzidis, Mercouri G.; Snyder, G. Jeffrey
Abstract: Superionic thermoelectric materials have been shown to have high figure-of-merits, leading to expectations for efficient high-temperature thermoelectric generators. These compounds exhibit extremely high cation diffusivity, comparable to that of a liquid, which is believed to be associated with the low thermal conductivity that makes superionic materials good for thermoelectrics. However, the superionic behavior causes cation migration that leads to device deterioration, being the main obstacle for practical applications. It has been reported that lithium doping in superionic Cu 2 − x Se leads to suppression of the Cu ion diffusivity, but whether the material will retain the promising thermoelectric properties had not yet been investigated. Here, we report a maximum z T > 1.4 from Li 0 . 09 Cu 1 . 9 Se, which is higher than what we find in the undoped samples. The high temperature effective weighted mobility of the doped sample is found higher than Cu 2 − x Se, while the lattice thermal conductivity remains similar. We find signatures of suppressed bipolar conduction due to an enlarged band gap. Our findings set forth a possible route for tuning the stability of superionic thermoelectric materials. Graphical abstract: Highlights: Copper selenide was doped with lithium to suppress the Cu ion diffusivity and enhance the reliability of the compound. Lithium doping shifts the onset temperature of bi-polar transport to a higher temperature, leading to a higher peak zT . The high temperature weighted mobility is found to follow the trend of acoustic phonon scattering. Lithium doping causes the superionic phase transition to occur sequentially which involves an additional intermediate phase.